Language Understanding and Knowledge of Meaning - Mitchell Green (Baltic International Yearbook of Cognition, Logic and Communication, 2009)
In recent years the view that understanding a language requires knowing what its words and expressions mean has come under attack. One line of attack attempts to show that while knowledge can be undermined by Gettier-style counterexamples, language understanding cannot be. I consider this line of attack, particularly in the work of Pettit (2002) and Longworth (2008), and show it to be unpersuasive. I stress, however, that maintaining a link between language understanding and knowledge does not itself vindicate a cognitivist view of the former.